Frequency of Uterine Rupture and Its Maternal and Fetal Outcomes of Uterine Rupture among Pregnant Women: Uterine Rupture among Pregnant Women - Seher, Aisha; Yousafzai, Arifa; Minhas, Zakia; Brohi, Sumera; Masood, Mehvish; Noor, Maryum; Fazal, Adnan (Pakistan Journal of Health Sciences, 2023)
A uterine rupture is when the uterine wall is torn during labor or right after birth. It is although not common but when occurs it is catastrophic obstetrical emergency for both mother and fetus needs prompt diagnosis and expert management. Moreover it may leads women to irreversible infertility as it rottenly ends at hysterectomy. Objective: To determine the frequency of uterine rupture and its maternal and fetal outcomes among pregnant women. Methods: This Cross Sectional study was conducted at Civil Hospital Karachi in the department of Obstetrics and Gynecology Unit II from 8th December 2018 to 7th June 2019. A total of 317 pregnant women of gestational age >28 weeks, fulfilling the inclusion criteria were enrolled .The data were collected on prepared proforma. Results: This study includes 317 patients with age ranges from 25 to 35 years with mean age of 28.44 ± 3.62 years. In this study, frequency of uterine rupture among pregnant women was found in 7(2.2%) women and maternal mortality 1(7.69%). Conclusions: Findings of this study suggests that uterine perforation is still high and remained important factor for maternal and fetal outcome.